Sclerosing polycystic adenosis of hard palate: A rare entity in salivary glands - Priyanka Guduguntla; Rajani Korlepara; Venkateswara Rao Guttikonda (Wolters Kluwer Medknow Publications, 2019)
Sclerosing polycystic adenosis (SPA) is a rare neoplasm of salivary glands, with a striking resemblance to the benign fibrocystic disease of the breast. The most common site of occurrence is the parotid gland. However, submandibular gland, minor salivary glands, and buccal mucosa may also be affected. It shows a slight female predilection and occurs over a wide age range. The exact nature of the disease is unknown but is postulated to be a neoplasm recently. The treatment is effective by localized surgical excision, and recurrence is rare. To the best of our knowledge, there is only one case report of SPA involving palate. Here, we describe an additional case report of SPA occurring in the palatal region of a 49-year-old male patient.